Chromatic Acclimation Processes and Their Relationships with Phycobiliprotein Complexes - Fanyue Wang; Min Chen (Microorganisms, 2022)
Chromatic acclimation (CA) is a widespread mechanism for optimizing the composition of phycobiliprotein complexes to maximize the cyanobacterial light capture efficiency. There are seven CA types, CA1-CA7, classified according to various photoregulatory pathways. Here, we use sequence analyses and bioinformatics to predict the presence of CA types according to three GAF (cGMP phosphodiesterase/adenylyl cyclase/FhlA)-containing photoreceptors, CcaS (cyanobacterial chromatic acclimation sensor), RcaE (regulator of chromatic adaptation), and RfpA (regulator for far-red photoacclimation). These photoreceptors were classified into three different phylogenetic groups leading different CA types in a diverse range of cyanobacteria. Combining with genomic information of phycobilisome compositions, the CA capabilities of various cyanobacteria were conjectured. Screening 65 accessible cyanobacterial genomes, we defined 19 cyanobacteria that have the capability to perform far-red light photoacclimation (FaRLiP) under the control of RfpA. Forty out of sixty-five cyanobacteria have the capability to perform green/red light photoacclimation, although they use different photoreceptors (RcaE and/or CcaS) and photoregulatory pathways. The reversible response of photoreceptors in CA regulation pathways trigged by changed light conditions reflects the flexibility of photoregulatory mechanisms in cyanobacteria and the putative independent evolutionary origin of photoacclimation types.